Global experiences in deleting zeros from the currency and the possibility of their application in Iraq - Ameen Tomas, Haqi (International Journal of Psychosocial Rehabilitation, 2020)
The Iraqi currency and the Central Bank of Iraq faced great challenges and a heavy legacy inherited from the previous regime. In light of the economic and financial conditions and the pressures of inflation that befell the country previously, great distortions were generated in the structures and economic relations, including the presence of a monetary block with many zeros of little value. after that was a job The central bank under the previous system is an institution for issuing currency to finance government expenditures, and after the promulgation of laws supporting the independence of the central bank in the new era, the central bank has had to reform the monetary system and take measures to restore the spirit of the Arab economy Defended for growth and prosperity, and one of these solutions is the process of deleting zeros from the Iraqi currency in order to control the flow and better manage the cost of the monetary block.